Dimensi Holistik Psikologi Sufi: Studi Perbandingan Psikologi Mainstream: The Holistic Dimension of Sufi Psychology: A Comparative Study with Mainstream Psychology - Al-Asyhar, Thobib; Gazali (Jurnal Bimas Islam, 2024)
This research explores the holistic dimension of Sufi psychology in comparison with mainstream psychology through a qualitative method based on descriptive analysis. The study maps the paradigm shift in mainstream (Western) psychology, from the humanistic approach focused on self-actualization, to the integrative approach offered by Sufi psychology combining holistic spiritual and psychological dimensions. Although mainstream (Western) psychology, as pioneered by Carl Rogers and Abraham Maslow, approaches the concept of psychological well-being with a comprehensive perspective, it is often trapped in reductionism that neglects the spiritual dimension. In contrast, Sufi psychology emphasizes four main elements—qalb (heart), ‘aql (intellect), ruh (spirit), and nafs (soul)—along with the concept of tazkiyah al-nafs (purification of the soul) as the primary strategy for achieving psychological and spiritual balance. This deeper and more comprehensive approach integrates divine values such as faith and tawhid in the process of healing and self-development, an approach that not only considers mental well-being but also spiritual well-being. In this context, Sufi psychology offers a solution to the spiritual and psychological crises of modern society by addressing the search for meaning in life and selftranscendence. Unlike Western psychological therapy, which is more focused on managing emotions and individual trauma, Sufi psychology emphasizes the importance of soul purification as a path to inner harmony and more holistic balance. The results of this study affirm the relevance of an integrative approach to meet the overall spiritual and psychological needs of humans, surpassing the limitations of materialism in Western mainstream psychology.